UPAYA PENINGKATAN HASIL BELAJAR MAHASISWA DALAM PEMBELAJARAN ATLETIK LARI 100 M MELALUI PEMANASAN MENGGUNAKAN PERMAINAN OLAHRAGA TRADISIONAL BENTENGAN - Rahmat, Ayi; Aryadi, Dedi (STKIP Setiabudhi, 2019)
Inadequate learning methods as well as inadequate learning process in the 100 m running athletic learning process result in student learning outcomes that are not optimal. The problem problem in research is